Respons Publik terhadap Isu Bendera One Piece di TikTok Menjelang HUT RI - Assadiyah, Diani (JURNAL NAWALA POLITIKA, 2025)
On the eve of the 80th Anniversary of the Republic of Indonesia, the hoisting of the One-Piece pirate flag (Jolly Roger) sparked a wide-ranging debate on social media, particularly TikTok. This popular culture symbol shifted from being merely a fictional icon to a symbolic political issue involving society, the media, and the government. This study aims to analyze public responses to TikTok content related to the One Piece flag within the framework of digital political communication. Using a descriptive qualitative approach, data were collected through observations of seven TikTok accounts discussing the issue, along with public interactions in the comment sections, supported by secondary sources from online media. The analysis refers to agenda-setting theory, digital political communication, and critical discourse analysis. The findings reveal that TikTok’s algorithm and user participation play a significant role in shaping the public agenda. Netizens’ responses reflect the tension between official nationalism and freedom of expression, while the One One Piece symbol is positioned as a space of ideological negotiation. These results highlight the role of social media as a dynamic arena of symbolic politics.